International Evidence on the Impact of Health-Justice Partnerships: A Systematic Scoping Review - Sarah Beardon; Charlotte Woodhead; Silvie Cooper; Elizabeth Ingram; Hazel Genn; Rosalind Raine (Frontiers Media S.A., 2021)
Background: Health-justice partnerships (HJPs) are collaborations between healthcare and legal services which support patients with social welfare issues such as welfare benefits, debt, housing, education and employment. HJPs exist across the world in a variety of forms and with diverse objectives. This review synthesizes the international evidence on the impacts of HJPs.Methods: A systematic scoping review of international literature was undertaken. A wide-ranging search was conducted across academic databases and grey literature sources, covering OECD countries from January 1995 to December 2018. Data from included publications were extracted and research quality was assessed. A narrative synthesis approach was used to analyze and present the results.Results: Reported objectives of HJPs related to: prevention of health and legal problems; access to legal assistance; health improvement; resolution of legal problems; improvement of patient care; support for healthcare services; addressing inequalities; and catalyzing systemic change. There is strong evidence that HJPs: improve access to legal assistance for people at risk of social and health disadvantage; positively influence material and social circumstances through resolution of legal problems; and improve mental wellbeing. A wide range of other positive impacts were identified for individuals, services and communities; the strength of evidence for each is summarized and discussed.Conclusion: HJPs are effective in tackling social welfare issues that affect the health of disadvantaged groups in society and can therefore form a key part of public health strategies to address inequalities.